Genetic Polymorphism in 220 bp Fragment of HSP 70 Gene in Kankrej Cattle by PCR-SSCP - Chaudhary, Dhavalkumar F.; Kharadi, V. B.; Ramani, Umed V.; Janmeda, Mamta; Pandya, G. M.; Baravaleeya, Krutiben; Koladiya, Hirali (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during January, 2022 to January, 2023 at the Department of Animal Genetics & Breeding, College of Veterinary Science and Animal Husbandry, Kamdhenu University, Navsari, Gujarat, India to identify polymorphisms in HSP 70 gene. Heat Shock Proteins (HSPs) known as molecular chaperones are essential for cells’ ability to recover from stress and serve as the primary defence mechanism within cells. They are extremely conserved and essential to the response to heat stress and cellular thermotolerance. Even though there are numerous HSP genes, in livestock species, heat tolerance is primarily associated with HSP 70. This gene polymorphisms have been linked to heat tolerance, milk production, fertility and cattle susceptibility to disease. They can be utilised as genetic markers to help choose animals that are more resilient to climate change, have stronger immune systems and perform better overall. A 220 bp fragment of bovine HSP 70 gene was subjected to Polymerase Chain Reaction- Single-Strand Conformation Polymorphism (PCR-SSCP) technique to identify the polymorphism. PCR-SSCP pattern was associated with the thermotolerance traits in Kankrej cattle using the univariate GLM model of SPSS 26. HSP 70 gene (220 bp fragment) was found to be monomorphic documented on SSCP gel which revealed only one genotype (AA) in all Kankrej cattle. It is concluded that genotype and its association with thermotolerance traits were found to be non-significant. However, The HSP 70 polymorphism is expected to strongly predict cattle heat tolerance, aiding in selection for thermotolerance.